The impact of preschool outdoor environment on children’s socio-emotional development - Mohamad, Norazlinda; Mohd Affandi, Haryanti; Saar, Massitah; Mustaffa Kamal, Mohd Firdaus; Mat Noor, Mohd Sallehuddin (Universiti Kebangsaan Malaysia, 2022)
Children are involved in various forms of social interactions, experiences, and the setting of environments in outdoor play areas that support children’s socio-emotional growth. It is necessary because the environment leaves a memorable experience for children. Other than that, it is crucial for their training and physical coordination. In addition, children’s emotional and social skills were indirectly assessed. This paper intends to incorporate an outdoor environment in preschools to meet the socio-emotional developmental needs of preschool children. Preschools located in Peninsular Malaysia were considered to be discussed in this paper. Conducting interviews with four teachers from various types of preschools can provide an initial picture of the external environment development in preschools. Early experiences of external environment interactions and the presence of social interactions with teachers and peers in preschool often impact the children’s learning experience. Two conclusions from the research findings guide the discussion on how the relationships of the preschools’ outdoor environment can foster the preschoolers’ socio-emotional growth. First, they acquire social and emotional competence with a combination of different experiences through shared or solitary experiences. Second, it was found that a variety of outdoor games with engaging spaces that offer attractions imminently stimulates game-based learning in contributing to the socio-emotional competence of preschoolers.